Pola dan Problematika Penyelenggaraan Achievement Grouping Class di SMU - Endang Poerwanti (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was focused on the implementation of Achievement Grouping Class in Senior High Schools (SMUs). Data were collected from pupils, teachers and principals of six SMUs in Malang Municipality. Using qualitative analysis, the study found out that the Achievement Grouping Class seemed to be able to accelerate the pupils' learning achievement. The system was applied by placing the high-achievers in one or two class(es) separated from the others. The interpersonal relationship within the regular classes was better than within the achievement classes dominated by interpersonal competition.